Empowerment of Mother's Groups to Improve Adolescent Reproductive Health in Kampung Nelayan Health Center - Siti Nurkholifah; Nikmatul Fadilah; Minarti Minarti; Intim Cahyono; Yohanes Kambaru Windi; Heru Sulistijono; Bambang Heriyanto; Asnani Asnani; Tumini Tumini; Dyah Wijayanti; Hasyim As'ari; Suriana Suriana; Baiq Dewi Harnani; Hilmi Yumni; Dinarwiyata Dinarwiyata; Eko Rustamaji; Ferry Kumala (Pusat Unggulan Ipteks Poltekkes Kemenkes Surabaya, 2023)
Now, adolescent reproductive health problems are increasing, which may be caused by a lack ofknowledge, self-confidence, religiosity and family support. So we need community service activities thataim to empower women's groups in improving adolescent reproductive health in the work area of theKampung Nelayan Health Center, Gresik Regency. Adolescents' commitment to maintaining reproductivehealth requires support from the family. Mothers are the closest people to their children, so mother'ssupport is an important component in improving adolescent reproductive health. This activity wasattended by 40 mothers of adolescents. The first stage was increasing knowledge, then mentoring andthe next was empowerment. The module on reproductive health as a media for health education wasfirst socialized to the mother group. The results of the activity showed that there was an increase in theknowledge and role of mothers in improving adolescent reproductive health.